Correlates of cannabis vape-pen use and knowledge among U.S. college students. (June 2018) - Frohe, Tessa; Leeman, Robert F.; Patock-Peckham, Julie; Ecker, Anthony; Kraus, Shane; Foster, Dawn W.
Abstract: Introduction: The proliferation of electronic devices, such as vape-pens, has provided alternative means for cannabis use. Research has found cannabis-vaping (i.e., vape-pen use) is associated with lower perceived risks and higher cannabis use. Knowledge of these products may increase likelihood of subsequent use. As policies for cannabis shift, beliefs that peers and family approve of this substance use (injunctive norms) increase and there has been an increase in vape-pen use among young adults (18–35 year olds); however, correlates thereof remain unknown. Young adults often engage in cross-substance use with cannabis and alcohol, making alcohol a potential correlate of cannabis vape-pen use and knowledge. Therefore, we examined alcohol use and other potential correlates of vape-pen use and knowledge among a sample of university students. Methods: This secondary data analysis utilized surveys at multiple colleges in the U.S. (N = 270). Alcohol use, social anxiety, cannabis expectancies, injunctive and descriptive norms and facets of impulsivity were examined as correlates of vape-pen use and knowledge using bivariate correlations and logistic regressions. Results: Alcohol use was correlated with cannabis vape-pen use and knowledge. Frequency of cannabis use, peer injunctive norms, and positive expectancies were associated with increased likelihood of vape-pen use. Lack of premeditation, a facet of impulsivity, was associated with cannabis vape-pen knowledge. Conclusions: Given the unknown nature and consequences of cannabis vape-pens, the present findings offer valuable information on correlates of this behavior. Further, correlates of knowledge of vape-pens may point to areas for education and clinical intervention to prevent heavy cannabis vape-pen use. Highlights: More cannabis use was related to higher odds of cannabis vape-pen use. Vape-pen use for cannabis was related to alcohol use. Each drink per drinking day related to 12 times greater likelihood of cannabis vape-pen use. Higher cannabis injunctive norms and expectancies predicted cannabis vape-pen use. Knowledge of cannabis vape-pens was associated with lack of premeditation.